О.І Nerovetskyi: The beginning of life journey of an outstanding civil engineer - H. H. Mykhailenko (History of science and technology, 2014)
The childhood and student’s years of an outstanding civil engineer, talented scientist and pedagogue professor O.I. Nerovetskyi are analyzed in the article (1884-1907).